Distribution of Cymbalaria muralis P. Gaertn., B. Mey. & Scherz. in the central part of Polish Pomerania - Truchan, Mariola; Sobisz, Zbigniew (Biodiversity: Research and Conservation, 2006)
This paper describes twelve new sites of Cymbalaria muralis found in 2003-2005 in the central part of Polish Pomerania. Four sites are situated in Słupsk and single sites are in Bytów, Jarosławiec, Lębork, Łeba, Sławno, Strzekęcin, Wieszyno and Zaleskie. C. muralis appears there on gothic defence walls, walls of old churches and castles, in slits of ports and canals, in joints of underpinnings of old houses, in stone slits of old wells, etc.